Knot-TPP: A Unified Deep Learning Model for Process Incidence and Tool Wear Monitoring in Stacked Drilling - Jiduo Zhang; Robert Heinemann; Otto Jan Bakker (Journal of Manufacturing and Materials Processing)
In drilling Carbon-Fibre-Reinforced Polymers (CFRP)/Al stacks, adaptive drilling facilitates the optimisation of cutting parameters for each constituent stack layer and tool wear, thus enhancing cutting efficiency and borehole quality. This study proposed a knot–Temporal Pyramid Pooling (TPP) model aimed at monitoring both process incidences and tool wear in the drilling of hybrid stacks, which subsequently informs the machine tool to adjust cutting parameters or, if necessary, replaces the tool. TPP is introduced to remove the restriction of input dimensions, allowing for the acceptance of inputs with arbitrary shapes. On the other hand, a knot structure has been proposed to incorporate the classification of process incidences into the tool wear analysis, thereby enhancing prediction accuracy. The proposed model achieves a process incidence identification accuracy of 99.19% and a Mean Absolute Error (MAE) of 10 μm in tool wear prediction, demonstrating robust performance across a wide range of sampling conditions. This achievement facilitates decision-making and optimisation relating to cutting parameters and tool replacement in the context of adaptive drilling of aerospace materials.